Identity and status of the human embryo - Sgreccia, Elio (Medicina e Morale, 1989)
The Steering Committee of the Catholic University's Bioethics Centre has already set out its position on the subject of prenatal diagnosis in a previous document (See ‘Medicina e Morale’ the Centre's official journal, 1987/6). During the 1988 study sessions, it brought its multidisciplinary reflection to bear on the subject of the identity, status and moral and legal protection of the human embryo. This theme in fact, authoritatively outlined in the first part of the ‘Instruction on respect for nascent human life and the dignity of procreation’ (Donum Vitae) of 22.2. 1987, is still at the basis of many bioethical debates, even beyond that of the voluntary interruption of pregnancy: in fact, the implications of certain artificial procreation techniques, experimentation on the embryo and the foetus, the removal of cells or tissues from them for grafting or transplantation into other subjects, prenatal diagnostics and in utero therapies, pose the problem of safeguarding the human embryo and require prior clarification on this crucial point. For more the debate....